Asistensi Legalitas Badan Hukum sebagai Upaya Penguatan Rencana Strategis BUM Nag Duo Baleh Suku dalam Pengembangan Usaha - Destuliadi Destuliadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to find out legal assistance for legal entities as an effort to strengthen the BUM Nag Duo Baleh Suku strategic plan in business development. This research method uses a qualitative descriptive approach. The results of the study show that the legality of Nagari-Owned Enterprises (BUM Nag) is a form of economic enterprise in Nagari or in other areas called BUMDes. BUM Nag Duo Baleh Suku has a profit and social business orientation, besides that it also functions as a facilitator and stabilizer that supports each other between the existing Natural Resources and Human Resources. BUM Nag Duo Baleh Suku has several business units including: Compost fertilizer business unit, animal feed processing business unit. Meanwhile, the strategic plan is to make BUM Nag a company that has good quality, develops production results and is a solid company. The conclusion of the research is that BUM Nag Duo Baleh Suku in business development already has a legal entity. According to Law No. 6 of 2014 concerning villages article 1 number 6 is a Nagari-Owned Enterprise (BUM Nag) whose entire capital is owned by the village originating from village wealth which is managed for the welfare of the village community. Keywords: Assistance, BUM Nag, Strategic Plan